Synthesis and Antimicrobial Activity of 2,3-(Substituted Phenyl) Pyrazine Dicarboxamide - Srinivasa Rao, N.; Raju, M.P.P.; Rao, J.T. (Asian Journal of Chemistry, 2010)
Pyrazine derivatives are synthesized from quinoline and screened for their antimicrobial activity against Eschericia coli, Bacillus substilis, Trichoderma sp. and Aspergillus niger.